2020
DOI: 10.1002/cncr.33287
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying treatment preferences and their association with financial toxicity in women with breast cancer

Abstract: BackgroundThe objective of the current study was to understand treatment preferences and their association with financial toxicity in Patient Advocate Foundation clients with breast cancer.MethodsThis choice‐based conjoint analysis used data from a nationwide sample of women with breast cancer who received assistance from the Patient Advocate Foundation. Choice sets created from 13 attributes of 3 levels each elicited patient preferences and trade‐offs. Latent class analysis segmented respondents into distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The ranges of median COST scores were large, from 10 to 29, in the various studies. 10 , 34 , 35 , 36 It is necessary to calculate the clinically significant cut-off value for financial toxicity in the various medical and health systems.…”
Section: Discussionmentioning
confidence: 99%
“…The ranges of median COST scores were large, from 10 to 29, in the various studies. 10 , 34 , 35 , 36 It is necessary to calculate the clinically significant cut-off value for financial toxicity in the various medical and health systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, our population is similar to samples of underresourced patients with cancer receiving financial aid. 38 A study using SEER data by Clegg et al found that cancer incidence and socioeconomic statuses (SES) differed among types of cancer: higher SES was found to be associated with prostate and breast cancer incidence, while lower SES was found to be associated with lung and colorectal cancer incidence. The lack of detailed information about current cancer treatment limits ability to evaluate impact by treatment type or phase of care nor if cancer care was delayed specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Excluded studies and reasons for exclusion are displayed in Supplementary Table 2. Hence, 34 studies were included in the analysis [ 19 , 31 63 ]. Figure 1 shows the flow chart of study selection according to the PRISMA statement.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are described in Supplementary Table 3. The studies were conducted in a variety of countries covering different health care systems: Australia [ 35 , 37 , 38 , 55 , 61 ], Belgium [ 54 ], Canada [ 42 , 45 , 58 , 60 ], France [ 54 , 59 ], Germany [ 53 , 54 , 57 , 62 ], Ireland [ 59 ], Italy [ 48 , 54 ], Japan [ 40 , 50 , 52 ], Lebanon [ 54 ], Peru [ 54 ], Poland [ 54 , 59 ], Portugal [ 54 ], Serbia [ 54 ], Slovenia [ 54 ], South Africa [ 54 ], South Korea [ 51 ], Spain [ 59 ], Switzerland [ 54 ], Taiwan [ 34 ], Thailand, the Netherlands [ 39 , 41 , 54 ], Turkey [ 54 ], the UK [ 36 , 54 ] and the USA [ 19 , 31 33 , 43 , 44 , 46 , 47 , 56 , 63 ]. Sample sizes ranged from 35 to 452 respondents included in the data analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation